Product Attributes, Price, and Promotion on Purchase Decisions of Halal Cosmetics with Religiosity and Halal Label as Moderation - Amalia Syafaatul Azka; Siti Jamilah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The cosmetics industry is experiencing significant growth, with halal cosmetics emerging as a critical segment driven by religious considerations. This study investigates the factors influencing halal cosmetic purchase decisions among Muslim consumers using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research explores the complex interplay between product attributes, price, promotion, religiosity, and halal labeling in shaping consumer purchasing decisions. Employing a survey method with 120 respondents, the study reveals that halal labeling is the most dominant factor in purchase decisions, with religiosity playing a crucial mediating role. Product attributes significantly influence religiosity, while price and promotion demonstrate minimal impact. The findings highlight that spiritual considerations and religious conformity far outweigh conventional commercial factors in halal cosmetic purchasing. This research provides valuable insights for marketers and manufacturers in understanding the nuanced decision-making process of Muslim consumers, offering both theoretical contributions and practical implications for the halal cosmetics market.